Aplikasi Berbasis Web Untuk Pelaporan Keuangan Toko Kue: (Studi Kasus: Kue Nova, Lampung) - Dolorosa Pratiknyo, Dhonie; Boing Kotjoprayudi, d Raswyshnoe (eProceedings of Applied Science, 2024)
Financial statements are records offinancial information of a company in anaccounting period that can be used todescribe the performance of the company.Financial statements are part of the financial reporting processfinancial reporting process which is usually oftenaudits by government agencies, accountants,firms, or other institutions with the aim ofensure accuracy and for tax purposes,financing, or investment purposes.